Implementasi Fungsi Manajemen Pada Pengelolaan Program Bantuan Operasional PAUD di Masa Pandemi Covid-19 - Baidowi, Ach. (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2020)
Management of organizational operational assistance funds is an effort to regulate the use of schools operational assistance funds so that their use is in accordance with school needs. The purpose of the research to describe the process of planning, organizing, implementing and controlling of operational assistance funds. The research approach is qualitative with data collection techniques namely interviews, observation and documentation. data analysis techniques with condensation, data presentation and drawing conclusions. The results show that planning is an activity of planning the use of operational assistance funds in schools, the organizing is the formatting of managers and grouping the use of operational assistance funds, implementation, namely the use of operational assistance funds for schools and controlling is checking the use of operational assistance funds. Abstrak Pengelolaan Bantuan Operasional Penyelenggaran merupakan usaha mengatur penggunaan dana bantuan operasional penyelenggaraan agar penggunaannya sesuai dengan kebutuhan sekolah. Tujuan penelitian untuk mendeskripsikan proses perencanaan, pengorganisasian, pelaksanaan dan pengontrolan pengelolaan dana Bantuan Operasional Penyelenggaraan. Pendekatan penelitian adalah kualitatif dengan teknik pengumpulan data yaitu wawancara, observasi dan dokumentasi serta teknik analisis data dengan kondensasi, penyajian data dan penarikan kesimpulan. Hasil menunjukkan perencanaan merupakan kegiatan merencanakan penggunaan dana bantuan operasional penyelenggaraan di sekolah, sedangkan pengorganisasian merupakan pembentukan pengelola dan pengelompokan penggunaan dana Bantuan Operasional Penyelenggaraan. Pelaksanaan yaitu penggunaan dana Bantuan Operasional Penyelenggaraan untuk sekolah dan pengontrolan merupakan pengecekan penggunaan dana Bantuan Operasional Penyelenggaraan.